2015
DOI: 10.1002/elps.201500192
|View full text |Cite
|
Sign up to set email alerts
|

Two‐photon excitation in chip electrophoresis enabling label‐free fluorescence detection in non‐UV transparent full‐body polymer chips

Abstract: One of the most commonly employed detection methods in microfluidic research is fluorescence detection, due to its ease of integration and excellent sensitivity. Many analytes though do not show luminescence when excited in the visible light spectrum, require suitable dyes. Deep-ultraviolet (UV) excitation (<300 nm) allows label-free detection of a broader range of analytes but also mandates the use of expensive fused silica glass, which is transparent to UV light. Herein, we report the first application of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…The spectrum of analytes accessible by fluorescence detection could be further extended if deep-UV light is used for excitation. In this case, UV-transparent fused silica chips , would need to be used instead of soda-lime glass, which absorb deep-UV light below 300 nm …”
Section: Resultsmentioning
confidence: 99%
“…The spectrum of analytes accessible by fluorescence detection could be further extended if deep-UV light is used for excitation. In this case, UV-transparent fused silica chips , would need to be used instead of soda-lime glass, which absorb deep-UV light below 300 nm …”
Section: Resultsmentioning
confidence: 99%
“…This is not only true for excitation at 266 nm in a one-photon approach but also for the detection of light at higher wavelengths for the two-photon equivalent at 532 nm. Previous studies on label-free detection utilizing PDMS chip materials revealed that full-body PDMS devices are not suitable for this purpose [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a typical 266-nm deep-UV source translates to excitation at 532 nm in the visible range. This is perfectly compatible with common chip materials [31][32][33][34] and optical elements, which also leads to less photostress in living cells [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…3 shows the optical transparency of different building materials such as fused silica, borosilicate glass, cyclic olefin copolymer (COC), cyclic olefin polymer (COP), PMMA and PDMS for microfluidic devices. 130 White et al developed a low-cost thermoplastic microfluidic chip using PMMA for SERS measurements. 125 Polymeric materials often suffer from poor chemical stability and exhibit Raman signals.…”
Section: Materials and Fabricationmentioning
confidence: 99%